Pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis Problem Based Learning terintegrasi Sustainable Development Goals (SDGs) pada Materi Koloid - Intan Klesya; Sofia Sofia; Eka Ad’hiya; Diah Kartika Sari (FKIP University of Mataram, 2026)
This study is a research and development (R&D) project aimed at producing a Student Worksheet (LKPD) based on Problem Based Learning (PBL) integrated with the Sustainable Development Goals (SDGs) on colloid material for Grade XI students. The research was conducted during the first semester of the 2024/2025 academic year, involving material experts, design experts, three students in the one-to-one evaluation stage, nine students in the small group stage, and one class in the field test. The development followed the Rowntree model consisting of planning, development, and evaluation phases. Formative evaluation was carried out using Tessmer’s model, which includes self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field test. The results indicate that the developed LKPD meets the criteria of validity based on expert judgment, practicality based on students’ and teachers’ responses, and effectiveness in improving students’ conceptual understanding of colloids and critical thinking skills. Therefore, the PBL-based LKPD integrated with SDGs is feasible and recommended for use as an innovative learning resource in high school chemistry classes.